Organization of science in Ukraine in the first half of the XIX century - Korobchenko, A. A. (History of science and technology, 2017)
In the article features of the organization of science in Ukraine in the first half of the 19th century are considered. In particular, it points to a special role in the dissemination of scientific knowledge of the first Ukrainian universities and scientific societies. It is proved that the first half of the 19th century became a period of significant achievements of scientists in the natural sciences. The main achievements of Ukrainian scientists in such sciences as botany, chemistry, geology, physics, mathematics and others are covered.